2023
DOI: 10.3390/cells12071002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Basic Fibroblast Growth Factor in Cancer: Biological Activity, Targeted Therapies, and Prognostic Value

Abstract: Cancer is the leading cause of death worldwide; thus, it is necessary to find successful strategies. Several growth factors, such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF, FGF2), and transforming growth factor beta (TGF-β), are involved in the main processes that fuel tumor growth, i.e., cell proliferation, angiogenesis, and metastasis, by activating important signaling pathways, including PLC-γ/PI3/Ca2+ signaling, leading to PKC activation. Here, we focused on bFGF, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 214 publications
0
6
0
Order By: Relevance
“…Moreover, FGF2 plays a crucial role in the development and function of multiple organ systems. Preclinical studies have shown that FGF2 improves myocardial perfusion, provides cardioprotection during ischemia‐reperfusion injury, and exhibits anti‐cardiac hypertrophy effects 13 . According to colocalisation‐IF, FGF2 might be an interactive factor of Thbs1 (Figure 4F).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, FGF2 plays a crucial role in the development and function of multiple organ systems. Preclinical studies have shown that FGF2 improves myocardial perfusion, provides cardioprotection during ischemia‐reperfusion injury, and exhibits anti‐cardiac hypertrophy effects 13 . According to colocalisation‐IF, FGF2 might be an interactive factor of Thbs1 (Figure 4F).…”
Section: Resultsmentioning
confidence: 96%
“…Preclinical studies have shown that FGF2 improves myocardial perfusion, provides cardioprotection during ischemia-reperfusion injury, and exhibits anti-cardiac hypertrophy effects. 13 According to colocalisation-IF, FGF2 might be an interactive factor of Thbs1 (Figure 4F). These findings demonstrate that…”
Section: Thbs1 Mediated Ecm-related Cytokines Via the Fgfr3/p-fgfr3 S...mentioning
confidence: 96%
“…Basic fibroblast growth factor (bFGF) can be involved in many biological processes such as angiogenesis, wound healing, neurogenesis, cellular differentiation and migration, and it can bind to all receptors ( 165 ). It has been found that the prepared bFGF-gel dressing effectively promotes wound healing in rats.…”
Section: Classification and Active Ingredients Of Dressingsmentioning
confidence: 99%
“…Furthermore, stimulation of EGFR can activate downstream transcription factors, such as hypoxia-induced factor 1 (HIF-1), which will stimulate the production of VEGF genes, genes that will trigger the synthesis of pro-angiogenic VEGF molecules via the translation process. Pro-angiogenic molecules, such as VEGF, bFGF, and HIF-1, are thus boosted through these several processes, promoting the proliferation, migration, and formation of new blood vessels [ 25 , 42 , 43 , 44 , 45 ]. Figure 1 depicts the several pathways that will be activated upon receptor stimulation that ultimately contribute to the process of angiogenesis.…”
Section: The Epidermal Growth Factor (Egf) Family Their Receptors And...mentioning
confidence: 99%